23-O-acetylshengmanol-3-O-α-L-arabinoside alleviates lipopolysaccharide-induced acute lung injury through inhibiting IκB/NF-κB and MAPK/AP-1 signaling pathways. (10th January 2023) - Chen, Chunyan; Li, Lin; Liu, Xiaomei; Zhang, Deqin; Liu, Yang; Li, Yuhong
Abstract: Ethnopharmacological relevance: Cimicifuga foetida L. is a well-established traditional Chinese medicine with heat-clearing and detoxifying effects and has good therapeutic effect on oral mucosal ulcer and pharyngitis. The rhizome of this herb is rich in triterpenoid glycosides, including 23-O-acetylshengmanol-3-o-α-L-arabinoside (DA). Aim of the study: Whether and how DA attenuates acute lung injury (ALI) are unclear. Accordingly, we focused on its anti-inflammatory effects and underlying molecular mechanisms in lipopolysaccharide (LPS)-stimulated ALI mice and RAW264.7 cells. Materials and methods: The model of ALI mice was established by exposed intratracheal instillation of LPS. Lung pathological changes were evaluated by hematoxylin and eosin staining. Pulmonary function was assessed by whole-body plethysmography. Total protein content in bronchoalveolar lavage fluid (BALF) was detected by bicinchoninic acid method. Wet/dry lung ratio was used to evaluate the degree of pulmonary edema in mice. The levels of pro-inflammatory mediators were measured using enzyme-linked immunosorbent assay. The relative expression of pro-inflammatory gene mRNA was examined by RT-qPCR. The expression of inflammatory-related proteins was detected by Western blot. RAW264.7 cells were used to test the anti-inflammatory effects of DA in vitro . Cytotoxicity was assessed using a MTT assay. Nitric oxide production was measured by Griess assay. The production and expression of inflammatory mediators and the protein levels of inflammatory signaling molecules in the NF-κB and MAPK pathways were measured. Furthermore, immunofluorescence staining was used to analyze the expression of p-IκBα, p-ERK, and p-p38 in lung macrophages and the nuclear translocation of NF-κB p65 and AP-1 in cells. Results: DA evidently alleviated histopathological changes and ameliorated pulmonary edema. Moreover, DA could reduce excessive inflammatory reaction in lung tissue as manifested by the reduction of proinflammatory mediators (IL-1β, IL-6, TNF-α, MCP-1, iNOS, and COX-2) in BALF, serum, and lung tissues. Further, DA inhibited the activation of the NLRP3/caspase-1 pathway in the lung. DA reduced the production and expression of the proinflammatory mediators above in RAW264.7 cells. Mechanistically, DA remarkably blocked the nuclear translocation of NF-κB p65, suppressed IκBα phosphorylation, and markedly reduced the nuclear translocation of AP-1 and the phosphorylation of ERK and p38. Conclusions: The findings demonstrated that DA exerts anti-inflammatory effects in LPS-stimulated ALI mice and macrophages by downregulating the NLRP3/caspase-1 signaling pathway in lung tissue and the IκB/NF-κB and MAPKs/AP-1 pathways in macrophages, suggesting that DA may be promising in ALI treatment. Graphical abstract: Image 1 Highlights: DA halted nonresolving inflammation in LPS-induced ALI mice. DA inhibited NLRP3 inflammasome activation in lung. DA inhibited macrophage activation by suppressing IκB/NF-κB and MAPK/AP-1 signaling pathways.